HISTORY OF THE COUNTRY WITHIN THE FRAMEWORK OF ACTIVITIES OF THE ASSEMBLY OF PEOPLE OF KAZAKHSTAN IN MODERN STUDY MATERIALS AND YOUTH EDUCATION (Journal of history, 2019)
The article is devoted to the unique experience of the Institute of the Assembly of People of Kazakhstan, which is a great representative of a unique example for young people, in particular in teaching various school and university academic disciplines. Using the experience of this institution in the framework of integration and interaction of all ethnic groups living in Kazakhstan, deserves a special attention. The experience of the Assembly of People of Kazakhstan contributes to the establishment and adoption of Kazakhstan model of a poly-ethnic society as a structure designed to ensure unity and harmony in a multi-ethnic country. Moreover, it is also an important source of the formation and development of civic identity and patriotic education of young generation.